Challenges of the Teaching Profession at MAN 1 Mataram in the Digital Era - Jumrotul Ismi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The education profession is a job that has expertise or ability in the field of education so that the educational process is carried out properly. Each profession will have a code of ethics and professional organization. The need for coaching for teachers at this time to be able to face challenges at this time and in the future. The method used in this study is a qualitative method using data collection techniques in the form of interviews, observations, questionnaires and document analysis. This research aims to find out what challenges are faced by teachers in the current era and provide education to the government to take the right steps for the development of education later.